Analisis Kepuasan SIAKAD Pondok Pesantren Miftahul Jannah Menggunakan System Usability Scale - Ahmad Arrijal Ismail, Ahmad Arrijal Ismail; Sanjaya, M Rudi; Saputra, Ariansyah (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
Information system of academic is a platform designed to manage academic data for educational institutions. The Miftahul Jannah Islamic Boarding School academic information system does not yet have a clear picture of the system satisfaction index. Satisfaction is an important factor in analyzing the system's ability to obtain data correctly and accurately. Given these challenges, a method is needed to assess satisfaction with SIAKAD Pondok Pesantren Miftahul Jannah. The purpose of this study is to assess user satisfaction with the Miftahul Jannah Islamic Boarding School Academic Information System (SIAKAD). The evaluation was conducted using the System Usability Scale (SUS) method In this study, the SUS method was used to measure user satisfaction with SIAKAD by involving the participation of 146 individuals from the boarding school. The results showed that SIAKAD of Miftahul Jannah boarding school received a score of 70.72, which indicates that the system is acceptable to users.